Produção de curativos hidrogel e wafer à base de polissacarídeos contendo nanopartículas de ouro sintetizadas in situ - Marques, Morgana Souza (2017)
Introduction: Among the curatives available for the treatment of cutaneous wounds, studies demonstrate the benefits of using hydrogel and wafers for dry and exudative wounds respectively. These dressings may serve as a matrix for delivering drugs directly into the wound site. Among the assets that can be incorporated, gold nanoparticles (AuNPs) have anti-inflammatory, antimicrobial and antioxidant properties that can support in the healing process. Objective: The objective of this work was to propose a simultaneous process of synthesis of AuNPs in a solution based on kappa carrageenan (κCG) and locust bean gum (LBG) to produce hydrogel and wafer dressings, applicable to the healing of cutaneous wounds. Methods: Synthesis and stabilization of AuNPs occurred simultaneously with the production of the dressing in κCG, LBG, glycerol (GLI) and/or polyvinyl alcohol (PVA) solution. Ultraviolet-visible spectroscopy, dynamic light scattering, rheological property, scanning electron microscopy, mechanical properties, infrared spectroscopy, swelling and antimicrobial activity were performed. Results: The red staining associated with characteristic surface plasmon resonance band confirmed the synthesis of AuNPs in κCG, LBG, GLI and PVA solution. The increase in Au3+ and PVA concentration are related to the larger and smaller AuNPs respectively. AuNPs interact with hydroxyl and sulfate groups and these interactions are associated with their stabilization and aggregation respectively. The increase in Au3+ concentration was responsible for the drop in viscosity and sol-gel transition temperature. The increase in Au3+ and PVA concentration reduced the mechanical properties of the wafers. Hydrogel and wafer swelled 130 and 660%, respectively, and were applicable in the treatment of mild to moderate dry and exudative wounds. Both synthesized devices did not present halos of inhibition against the microorganisms studied. Conclusion: Solution of κCG, LBG, GLI and / or PVA presents reducing and stabilizing power in the synthesis of AuNPs being able to simultaneously form hydrogels and wafers with potential application in the healing of cutaneous wounds.